Incentives in supply function equilibrium - Henrik Vetter (Economics: The Open-Access, Open-Assessment E-Journal, 2015)
The author analyses delegation in homogenous duopoly under the assumption that firm-managers compete in supply functions. He reverses earlier findings in that owners give managers incentives to act in an accommodating way. That is, optimal delegation reduces per-firm output and increases profits to above-Cournot profits. Moreover, in supply function equilibrium, the mode of competition is endogenous. This means that the author avoids results that are sensitive with respect to assuming either Cournot or Bertrand competition.
Keywords: D22; D43; L22; 330; Delegation; incentives; supply function equilibrium